\(α\)-STRONG PRECOMPACTNESS IN FUZZY TOPOLOGICAL SPACES - Krsteska, Biljana (Matematichki Bilten, 1999)
A concept of an \(α\)-strong precompactness in fuzzy topological spaces is introduced and studied. Three countable properties of fuzzy topological spaces are introduced and investigated by the help of fuzzy strongly preopen sets.